1995
DOI: 10.2166/wst.1995.0514
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for dissolved air flotation in water and wastewater treatment

Abstract: A kinetic model for DAF is presented. The author's kinetic model consists of the equations for describing a process of bubble-floc collision and attachment in a mixing zone, and a rise velocity of bubble-floc agglomerates in a flotation tank. The attachment process is formulated on a population balance model with bubbles and flocs as a flocculation in a turbulent flow. The rise velocity of bubble-floc agglomerates is formulated with size of flocs and composition of flocs including the floc density function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
12

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 3 publications
1
46
1
12
Order By: Relevance
“…But large flocs are not necessary for flotation since bubbles and particles need to be attached, and particle-bubble agglomerate density should be reduced to less than water [21,45]. Literature agrees on the flocculation time reduction from 20 to 30 min in the conventional sequence (C/F/S) to 5-10 min in the DAF sequence (C/F/DAF) [3,20,22,23,25]. Edzwald et al [4] results showed that good flotation performance was achieved with either 8 or 16 min for flocculation, so shorter times 5-8 min should be adequate.…”
Section: Effects Of Velocity Gradient Retention Time and Pressurisedmentioning
confidence: 99%
See 2 more Smart Citations
“…But large flocs are not necessary for flotation since bubbles and particles need to be attached, and particle-bubble agglomerate density should be reduced to less than water [21,45]. Literature agrees on the flocculation time reduction from 20 to 30 min in the conventional sequence (C/F/S) to 5-10 min in the DAF sequence (C/F/DAF) [3,20,22,23,25]. Edzwald et al [4] results showed that good flotation performance was achieved with either 8 or 16 min for flocculation, so shorter times 5-8 min should be adequate.…”
Section: Effects Of Velocity Gradient Retention Time and Pressurisedmentioning
confidence: 99%
“…However, some authors disagree on the efficiency of these small size flocs in the C/F/DAF process. Fukushi et al [20] agreed that long flocculation is not needed, but they considered that larger flocs have a much higher collision efficiency, hence larger flocs should be prepared for effective DAF. Furthermore, Vlaski et al [24] concluded that the increase of the larger floc size fraction achieved by low flocculation G values resulted in relative floc density decrease, and in higher DAF efficiencies.…”
Section: Effects Of Velocity Gradient Retention Time and Pressurisedmentioning
confidence: 99%
See 1 more Smart Citation
“…In dispersed air flotation the bubbles are on the order of 1 mm in diameter and the flow around the bubble can be modeled using potential flow theory. This paper considers the collision efficiency between a bubble and a particle in microbubble flotation with particular emphasis on dissolved air flotation used for potable water treatment where the particles to be removed are typically of the same size as the bubbles (1). In dissolved air flotation bubbles are produced by first saturating water with air at high pressure and then subsequently reducing the pressure which causes the supersaturated dissolved air to come out of solution in the form of microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the resulting bubble-particle agglomerate must be positively buoyant and rise to the top of the flotation tank before bubble-particle detachment, or, in the case of a continuous throughput tank, before the bubble-particle agglomerate is carried out of the flotation tank in the effluent stream. The removal efficiency E of an isolated bubble-particle interaction is typically decomposed as (2) E ϭ E c E a ͑1 Ϫ E d ͒, [1] where E c represents the collision efficiency between a bubble and a particle, E a represents the probability that a given bubble-particle collision results in successful bubble-particle attachment, and E d represents the probability of bubble-particle detachment before the bubble-particle agglomerate rises to the foam layer. In this paper the focus is on modeling the close approach of the bubble and particle under the influence of gravity and interparticle forces and on calculating collision efficiencies.…”
Section: Introductionmentioning
confidence: 99%